2020
DOI: 10.1016/j.ymgmr.2020.100671
|View full text |Cite
|
Sign up to set email alerts
|

Phenylketonuria in the Latvian population: Molecular basis, phenylalanine levels, and patient compliance

Abstract: Introduction Phenylketonuria (PKU) is an inborn error of metabolism characterized by pathogenic variants of the phenylalanine hydroxylase ( PAH ) gene with a resulting accumulation of phenylalanine (Phe) to neurotoxic levels. Diagnosis of PKU in the Latvian population began in 1985 and the present study's aim was to evaluate the available data on all PKU patients in Latvia. Materials and methods The medical records of 116 - DNA sample was avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Poor adherence in adolescent and adult PKU patients was also reported by Jurecki et al who observed a suboptimal adherence to the recommended Phe concentrations [ 14 ]. At present, there is a significant lack of information on the nutritional status of Latvian adolescent and adult (over the age of 18) PKU patients [ 15 ]. The reason for this is their non-compliance with completing a 72-h FD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poor adherence in adolescent and adult PKU patients was also reported by Jurecki et al who observed a suboptimal adherence to the recommended Phe concentrations [ 14 ]. At present, there is a significant lack of information on the nutritional status of Latvian adolescent and adult (over the age of 18) PKU patients [ 15 ]. The reason for this is their non-compliance with completing a 72-h FD.…”
Section: Discussionmentioning
confidence: 99%
“…In some patients, their Phe levels were above 360 mmol/l; therefore, their intake of natural protein could not be as low as detailed in their FD. [ 15 ] Additionally, inconsistencies were seen with BMI and FD data on CHO and total energy intakes. Specifically, three obese patients reported CHO and total energy intakes that were lower than the values recommended by the MHRL.…”
Section: Discussionmentioning
confidence: 99%
“…The blood sample is tested in a laboratory to determine if it has too much phenylalanine in it.) [ 23 ]. The inclusion criteria for patients in the control group were as follows: healthy individuals matched by age and gender with the T1D and PKU groups, not following any specific diet, no chronic diseases, and seen for regular dentist checkups.…”
Section: Methodsmentioning
confidence: 99%
“…PKU is a metabolic condition in which the inability to degrade phenylalanine (Phe), an essential amino acid, results in irretrievable psychological retardation unless treated early. As a result, early detection and dietary treatment through new-born screening program, the negative impacts such as mental retardation of the disease can be largely eliminated [8,9]. For establishing new-born screening programs of PKU patients in the United Kingdom, Robert Guthrie developed a classical method for the detection of high levels of Phe in blood shortly after a baby born by using a bacterial inhibition assay [10].…”
Section: World-wide New-born Screening Programmentioning
confidence: 99%